THE INFLUENCE OF STUDENTS' LEARNING ACTIVENESS ON STUDENTS' LEARNING ACHIEVEMENT AT SMAN 1 TASIK PUTRI PUYU LOKAL JAUH - Mega Dahlia; Ade Silvana; Noval Fadli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This research is entitled the Influence of the Students' Learning Activeness on Students' Learning Achievement at SMAN 1 Tasik Putri Puyu Lokal Jauh. The aim of this research was to find out whether there was a significant influence of the students' learning activeness on students' learning achievement. This research used a quantitative method with a correlational approach. The population in this study was the students of SMA N 1 Tasik Putri Puyu Lokal Jauh, with a total of 73 students, the samples for this reseach were students of class XI IIS 3 with a total of 22 students. Sampling was carried out using a purposive sampling technique. The data obtained were analyzed using the Pearson correlation test to test the influence of the independent variable (Students' Learning Activeness) on the dependent variable (Students' Learning Achievement). Data was collected through a questionnaire consisting of 31 statements and a test given at the end of each lesson. The results of this research showed that the value of r count (0.281) r table (0.4227) which means that Alternative Hypothesis (Ha) is rejected and Null Hypothesis (Ho) is accepted. This research shows that there is no significant influence between the Students' Learning Activeness and Students' Learning Achievement. Based on this, it is recommended that further research consider other variables that are more relevant to Students' Learning Achievement. Key words: learning achievement, active learning, quantitative, correlation